6 - hour guide to protecting your assets : - Shenkman, Martin M. (John Wiley, 2003)
SIMPLE, AFFORDABLE STEPS YOU CAN TAKE TO PROTECT WHAT'S YOURS By the time you're named as a defendant in a lawsuit or divorce proceeding, it may be too late to protect your assets. The time to shield the hard-won fruits of your labor is now! Fortunately, protecting your assets can be much easier and far less expensive than you think. In this complete, practical, and easy-to-follow guide, leading tax and estate planning attorney and bestselling author Martin Shenkman presents the steps you can and should take to protect your home, your savings, and other assets from creditors, litigants, and divorce. Shenkman explains the essential concepts of protecting what you own from malpractice claims, lawsuits, and divorce. This book offers step-by-step guidance in determining which asset-protection strategies and techniques are right for you. You'll learn numerous legal and effective methods you can use to: Protect your personal assets from business and professional claims Protect your assets and your heirs' assets from divorce Minimize your risk of lawsuits and other claims against your assets Create limited partnerships and LLCs to protect your assets Make your home-based business judgment-proof Use domestic trusts to protect against lawsuits Secure real estate and stock holdings against lawsuits